Citogenômica de pterodon pubescens e citogenética comparativa com P. emarginatus (leguminosae) - Albernaz, Victória Borges (2020)
The genus Pterodon Vogel (Leguminosae) has only four species, of which P. pubescens (Benth.) Benth. and P. emarginatus Vogel (both known as "white sucupira") are the closest phylogenetically. These species have a wide geographical distribution in Brazil and have chromosome number 2n = 16 with small and morphologically similar chromosomes. The objective of the present work was to carry out a comparative analysis of the genome size, the banding pattern and the composition of repetitive elements in the chromosomes of P. pubescens and P. emarginatus, aiming to enhance the cytogenomic and evolutionary knowledge of these species. For this, cytogenetic characterization was performed by analyzing the number and chromosomal morphology, CMA and DAPI banding, hybridization with DNAr 5S and 35S and determining the genome size by flow cytometry. In addition, we used P. pubescens genome sequencing by NGS (Next Generation Sequencing) using the Illumina platform to characterize repetitive genomic fractions, using a Galaxy/RepeatExplorer-Elixir platform. The most abundant elements of the P. pubescens genome were located on the chromosomes by fluorescent in situ hybridization (FISH) and transferred to P. emarginatus. The species showed very similar karyotypes with: (i) CMA+/DAPI- bands in the terminal region of two chromosome pairs and pericentromeric region of all chromosomes; (ii) two pairs of 35S rDNA sites co-located with the terminal CMA+ bands; (iii) a pair of 5S rDNA sites located in the proximal region of a chromosomal pair. The genome size of P. pubescens and P. emarginatus was also similar, 1C = 0.665 pg and 1C = 0.620 pg, respectively. The repetitive fraction represented 26,4% of the P. pubescens sequenced genome, with Ty3-Athila Ty3-Athila (24,24%), Ty3-Tekay (21,93%) and Ty1-Ale (3,37%) retrotransposons being the most abundant elements. Low abundance satellite DNAs were identified: PubSat1-254 (2,09%), PubSat2-76 (2,06%), PubSat3-216 (0,58%), PubSat4-138 (0,23%). In situ hybridization reveal that all analyzed repeats were enriched in proximal CMA+ heterochromatin in both species, except for the Ty1-Ale retroelement, which was also dispersed also in the euchromatin of P. pubescens chromosomes. The cytomolecular similarity observed here suggests that the genomes of P. pubescens and P. emarginatus have highly similar repetitive fractions, which corroborates their phylogenetic proximity. However, the recent expansion of the Ty1-Ale element in the P. pubescens genome suggests some degree of differentiation in the repetitive fractions of these genomes.